Integrated BIM, game engine and VR technologies for healthcare design: A case study in cancer hospital. (April 2018) - Lin, Yu-Cheng; Chen, Yen-Pei; Yien, Huey-Wen; Huang, Chao-Yung; Su, Yu-Chih
Abstract: The results of healthcare design should meet the requirements of design teams as well as healthcare stakeholders. However, misunderstandings that occur between the design teams and healthcare stakeholders when using 2D illustrations leads to the need for re-design and rework during the design phase. To overcome this problem, this study develops a Database-supported VR/BIM-based Communication and Simulation (DVBCS) system integrated with BIM, game engine and VR technologies for healthcare design special in the Semi-immersed VR environment. The DVBCS system is applied in a case study of a design project of a cancer center in Taiwan to verify the system and demonstrate its effectiveness in practice. The results demonstrate that a DVBCS system is an effective visual communication and simulation platform for healthcare design. The advantage of the DVBCS system lies not only in improving the communication efficiency between the design teams and healthcare stakeholders, but also in facilitating visual interactions and easing the decision-making process while communicating in the 3D VR/BIM environment. The effective use of the proposed DVBCS system will assist design teams and stakeholders significantly in systematically handling healthcare design work in future healthcare design.